HIV Testing in Correctional Agencies and Community Treatment Programs: The Impact of Internal Organizational Structure - Oser, Carrie B. (2007)
This study compares the provision of HIV testing in a nationally representative sample of correctional agencies and community-based substance abuse treatment programs and identifies the internal organizational-level correlates of HIV testing in both organizations. Data are derived from the CJ-DATS’ National Criminal Justice Treatment Practices Survey (NCJTP). Using an organizational diffusion theoretical framework (Rogers, 2003), the impact of Centralization of Power, Complexity, Formalization, Interconnectedness, Organizational Resources, and Organizational Size on HIV testing was examined in correctional agencies and treatment programs. While there were no significant differences in the provision of HIV testing among correctional agencies (49%) and treatment programs (50%), the internal organizational-level correlates were more predictive of HIV testing in correctional agencies. Specifically, all dimensions, with the exception of Formalization, were related to the provision of HIV testing in correctional agencies. Implications for correctional agencies and community treatment to adopt HIV testing are discussed.